"Shared Decision Making Assistant": A Smartphone Application to Meet the Decision-Making Needs of Patients With Primary Liver Cancer. Issue 12 (3rd December 2021) - Wang, Sitong; Ye, Zhixia; Pan, Zeya; Yang, Ning; Li, Yu; Li, Yunyun; Li, Li
Abstract : The development of medical technology provides medical specialists with a variety of choices for their primary liver cancer patients, including partial liver resection, transcatheter arterial chemoembolization, liver transplantation, and so on. However, in this context, because patients with primary liver cancer frequently do not receive adequate information to help make complicated medical decisions, those patients, who are usually otherwise ignorant about their disease, are facing multiple difficult choices. The problem might be alleviated with a process called "shared decision making." Accordingly, researchers developed a smartphone application named "Shared Decision Making Assistant" for primary liver cancer patients in China, and in this article, we report the process of its development. First, individual interviews were conducted to identify the specific needs and status of primary liver cancer patients participating in shared decision making. Next, expert group discussions were held among primary liver cancer medical experts, nurses, and software engineers, using a decision-making process called the Delphi method, which was used to arrive at a group opinion or decision by surveying a panel of experts, to draft the framework and decide on the contents of the mobile health–based decision aids program. Feedbacks and suggestions were collected to optimize the workflow of "Shared Decision Making Assistant." The resulting application consisted of seven modules: personal information, primary liver cancer treatment knowledge center, decision aids path, continuing care, interactive platform, health education, and backstage management.